Peraturan Perundang-Undangan di Indonesia Terkait Perlindungan Konsumen Terhadap Iklan Produk Rokok - Ismail, Abil Fida; Nugroho, Widhi Cahyo (Media Hukum Indonesia (MHI), 2024)
One of the reasons for the high prevalence of child smoking is the massive advertising of cigarette products circulating in various media, whether in print, broadcast, information technology, and/or outdoors, providing exposure to children who see it. Legal protection for child smokers as consumers in order to reduce the prevalence of child smokers has been regulated in regulations containing control over advertisements for cigarette products, however research results state that children can still access cigarette advertisements spread on social media, especially electronic cigarette advertisements. There is not a single business actor who does not advertise their products, whether the products are made from herbal ingredients, synthetic ingredients, or even dangerous ingredients. Advertising itself can be done in various ways, and one method that is currently very popular with business people is by advertising their products through television and social media. Cigarette advertising itself has been deemed to have committed several violations of business ethics. This research aims to determine the views of Indonesian laws and regulations regarding cigarette advertising and regarding efforts to protect consumers regarding advertising of cigarette products in an effort to reduce the prevalence of child smoking and whether or not there are violations of business ethics that occur when cigarette advertisements are shown on television. The research results show two types of business ethics violations, namely those that occur when cigarette advertisements are broadcast; The two types of violations are moral violations and empathy violations. Moral Violations occur because of the ineffectiveness of restrictions on advertising cigarettes that have been set by the government.